Oxygen‐Insensitive Peroxide Reduction Catalysts for Reliable Electrochemical Bioassays. Issue 7 (30th January 2022) - Ding, Zhenyao; Wang, Dandan; Chen, Liping; Zhou, Hang; Zhang, Xiqi; Feng, Xinjian; Jiang, Lei
Abstract: Coupling the oxidase enzymatic and H2 O2 cathodic reactions is an ideal approach for accurate bioassays development because it naturally avoids most endogenous/exogenous electroactive interferents in biofluids. However, the accompanying oxygen cathodic reaction at the surface of commonly used stable catalysts compromises the bioassay accuracy, thus limiting practical application of this detection principle. Here, highly active oxygen‐insensitive electrocatalysts for H2 O2 reduction by modifying noble metals (Pt, Au) with an ultra‐thin tin oxide layer that can selectively block the diffusion of oxygen from the electrolyte to the noble metal surface, are reported. This empowers the electrocatalysts with enhanced resistance to current interference from oxygen reduction reaction, thus enabling highly selective sensing of sarcosine, a model analyte (a biomarker for prostate cancer), in the presence of various electroactive interferences. This work highlights the importance of H2 O2 cathodic reactions in accurate biomarker detection and their advanced applications in life science, including developing reliable biomarker assays. Abstract : The oxygen‐insensitive electrocatalysts involving noble metal and ultrathin amorphous SnO x layer enable the great peroxide reduction selectivity over oxygen reduction owing to the perm‐selectivity function of the SnO x . Based on these catalysts, high cathodic H2 O2 detection accuracy in fluctuant oxygen concentrations and toward numerous endogenous/exogenous interferents is realized.